Highly efficient perovskite solar cells with crosslinked PCBM interlayers. Issue 6 (20th January 2017) - Qiu, W.; Bastos, J. P.; Dasgupta, S.; Merckx, T.; Cardinaletti, I.; Jenart, M. V. C.; Nielsen, C. B.; Gehlhaar, R.; Poortmans, J.; Heremans, P.; McCulloch, I.; Cheyns, D.
Abstract : PCBM crosslinked with 1, 6-diazidohexane (DAZH) was introduced to solve the solvent incompatibility of depositing a solution processed perovskite layer onto it. Abstract : Commercially available phenyl-C61 -butyric acid methyl ester (PCBM) is crosslinked with 1, 6-diazidohexane (DAZH), resulting in films resistant to common solvents used in perovskite solar cell processing. By using crosslinked PCBM as an interlayer and (HC(NH2 )2 )0.66 (CH3 NH3 )0.34 PbI2.85 Br0.15 as the active layer, we achieve small area devices and modules with a maximum steady-state power conversion efficiency of 18.1% and 14.9%, respectively.